1995
DOI: 10.1080/02688699550041511
|View full text |Cite
|
Sign up to set email alerts
|

Primary cerebral gliosarcoma: report of 17 cases

Abstract: A retrospective study of 17 cases of primary cerebral gliosarcoma is presented. These uncommon highly aggressive intracranial neoplasms were seen at the Royal Preston Hospital, between 1973 and 1992. The patients' ages ranged from 21 to 73 years (mean 52), nine were males and eight were females. They presented with signs and symptoms of a rapidly expanding brain tumour. The diagnosis was suspected on radiological findings and confirmed by histological examination. Treatment involved surgical excision in 15 cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
39
0
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 17 publications
3
39
0
1
Order By: Relevance
“…5,10,[12][13][14][15][16][17] However, the majority of these studies did not specify a diagnosis of PGS, and included a mixture of both de novo and secondary gliosarcomas. The report by Perry et al in 1995 suggested a more favorable prognosis in patients with secondary gliosarcoma, underscoring the importance of keeping the primary type and gliosarcoma diagnosed at disease recurrence of prior malignant glioma distinct.…”
Section: Discussionmentioning
confidence: 99%
“…5,10,[12][13][14][15][16][17] However, the majority of these studies did not specify a diagnosis of PGS, and included a mixture of both de novo and secondary gliosarcomas. The report by Perry et al in 1995 suggested a more favorable prognosis in patients with secondary gliosarcoma, underscoring the importance of keeping the primary type and gliosarcoma diagnosed at disease recurrence of prior malignant glioma distinct.…”
Section: Discussionmentioning
confidence: 99%
“…Gliosarcoma is a rare glial tumor which accounts for 1.8-8% of glioblastomas [7,15,17,24] with an estimated annual incidence in Europe and the USA of one case per million inhabitants [14]. Gliosarcomas generally appear in the brains of adult patients.…”
Section: Discussionmentioning
confidence: 99%
“…According to the 2010 statistical analysis by the Central Brain Tumor Registry of the United States, from 2004 to 2006, GBM accounted for 53.8% of all Gliomas, Gliosarcomas accounted for 2% of all GBM. The epidemiology and natural history of Gliosarcomas are similar to Glioblastoma (4,5,6) . Males are more frequently affected than females (M: F ratio 1 …”
Section: Introductionmentioning
confidence: 91%